Formalization of the mathematical modeling process of adaptive change of code structure in wireless data transmission - Horlynskyi, Borys V.; Zaitsev, Sergei V.; Kaznadiy, Svitlana P.; Zaitsevа, Lilia I. (Kyiv National University of Construction and Architecture, 2019)
The formalization of the process of structural adaptation of turbo codes under the conditions of noise interference, which lead to uncertainty in the process of decoding of correction codes, is proposed. The essence of formalization lies in the adaptive choice of the structure of the correction code using the a priori and a posteriori information of the decoder at the expense of minimizing the average risk. The proposed results can be used to ensure the reliability of information transfer systems that operate in the face of powerful interference.